1992
DOI: 10.1117/12.132042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and nonlinear optical properties of sol-gel materials containing phthalocyanines

Abstract: Optical limiters are devices that have the ability to limit the intensity of light that passes through them. They function like 'optical surge protectors,' blocking a greater fraction of photons when the incident light intensity is very high than when the incident intensity is low. This might allow an electronic sensor or a human eye to function under ambient lighting conditions and yet be protected from being blinded by direct laser ifiumination.Phthalocyanine (Pc) dyes which exhibit nonlinear optical behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…). [337] The final nonlinear properties are comparable to the one in buffer solution. In the same period investigations on the use of polymeric matrices were reported.…”
Section: Dispersion Of Dyes In Sol-gel or Organic Materialssupporting
confidence: 60%
See 1 more Smart Citation
“…). [337] The final nonlinear properties are comparable to the one in buffer solution. In the same period investigations on the use of polymeric matrices were reported.…”
Section: Dispersion Of Dyes In Sol-gel or Organic Materialssupporting
confidence: 60%
“…The dispersion of metallophtalocyanine dyes with interesting RSA into SiO 2 sol-gel matrices was firstly reported. [157,337] The RSA of the dyes was also observed in the solid materials demonstrating the capacity of the strategy. The presence of dimers showed that the dyes were not totally homogeneously dispersed, and protonated species which showed that the process should be adapted to the dyes sensitivity (Control of pH .…”
Section: Dispersion Of Dyes In Sol-gel or Organic Materialsmentioning
confidence: 75%
“…19 An alternative experimental setup involves an ultrasonic bath. 83 In these cases a much lower ultrasonic intensity is supplied to the reactants and, consequently, the resulting samples do not offer the characteristic sonogel features.…”
Section: Sonogelsmentioning
confidence: 99%
“…An alternative experimental setup involves the use of an ultrasonic bath [50]. In these cases, a much lower ultrasonic intensity is supplied to the reactants and, consequently, the resulting samples do not offer the characteristic sonogel features.…”
Section: Experimental Alternativesmentioning
confidence: 99%